The best book of dinosaurs - Maynard, Christopher (New York : Kingfisher, 1998)
Introduces dinosaurs and their world, discussing such topics as their food, life cycles, means of hunting, and means of fighting and defense.
Includes index.
Library Talk.
4.8
K-3
Keywords: Dinosaurs -- Juvenile literature; Dinosaurs; Dinosaurs; Dinosaurs